Media Pembelajaran Interaktif Serat Wulangreh Pupuh Gambuh Berdialek Ngapak - Dewi, Sisi Milawati; Mujimin, Mujimin; Widodo, Widodo (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
The language in the Wulangreh pupuh Gambuh fiber uses the archaic word, while what the students understand is Javanese, the Ngapak dialect. At SMP N 2 Mrebet, there were obstacles that generally occurred in learning Wulangreh pupuh Gambuh fibers, including 1) students did not know the titi laras so that when serving wulangreh pupuh Gambuh fibers students did not master it 2) students did not know the contents of the Wulangreh pupuh Gambuh fiber. The purpose of this study is to describe the needs of teachers and students, compile a media prototype design, and describe the results of expert validation. Sources of data from this study were students of class VIII SMP N 2 Mrebet, Javanese language teachers, and experts. Data collection techniques are carried out by interview, questionnaire, and expert assessment sheets. The data analysis technique in this study used a qualitative descriptive technique. The results of the needs of students and teachers state that there is a need for new media references that are more interesting and complete so that they can guide students in studying the fiber material of Wulangreh pupuh Gambuh. The media prototype developed has several characteristics, including (1) the language of instruction uses the ngapak dialect (2) helps students practice nembang (3) illustrated tembang stories that are presented using the ngapak dialect (4) the backsound uses the song ngapak and gendhing Banyumsan (5) provided fiber Wulangreh pupuh Gambuh with cakepan using the ngapak dialect (6) the graphic symbol used is a symbol of the Purbalingga area. Based on the expert's assessment, the Pupuh Gambuh Berdialek Ngapak Interactive Learning Media is considered suitable for use with several improvements.